'Aren't we mothers all the same?': Personhood and patria in Eva Canel's La mulata. Issue 8 (1st September 2022) - MATEOS, ANA
Abstract : Eva Canel's play La mulata (Barcelona 1891, premiered in Havana in 1893) places its protagonist, Patria, at the intersection of feminist, anti-racist and anti-colonial agendas. In particular, I argue that it is through an original adaptation of the sentimental ideal of motherhood that the play grounds Patria's rights as a mother and as an Afro-descendant woman, as well as the standing of a soon to be independent Cuba. In this way, the play invites reflection on the problematic relationship between discourses of disembodied personhood and bodily discrimination.